Thermal behaviour of Paraffin-MWCNT stabilized by Sodium dodecylbenzene sulphonate nano-enhanced phase change material for energy storage applications - Bhutto, Yasir Ali; Pandey, Adarsh Kumar; Saidur, Rahman Md; Laghari, Imtiaz Ali; Buddhi, D.; Tyagi, Vineet Veer (Institute of Physics, 2023)
The Phase change materials (PCMs) possess the great potential to store renewable and sustainable thermal energy that can mitigate the issue of energy to a great extent. However, the low thermal conductivity hinders the extensive use of PCM in various applications. To alleviate this deficiency, the PCMs are often incorporated with highly conductive nanoparticles. The carbon-based nanoparticles are highly regarded to be a promising option because of their elevated thermal conductivity like Multiwall carbon-nanotube (MWCNT). However, these highly conductive nanoparticles sometimes exhibit the issue of non-uniform dispersion with PCM. In this paper, we report the use of surface-modified MWCNT by using stabilized Sodium dodecylbenzene sulphonate surfactant (SDBS) with Paraffin wax (PW) RT47 at wt% 0.1 and 0.3 of MWCNT. The sample is created by using two-step method. Further, for characterization; chemical composition by Fourier transform infrared spectroscopy (FTIR), thermal conductivity by thermal property analyzer (TEMPOs) and for thermal stability, thermal gravimetric analyzer (TGA) is used. The results showed a significant enhancement in the thermal conductivity of composite PCM, the inclusion of 0.1 and 0.3 wt% of surface-modified MWCNT increased the thermal conductivity up to 51.29% and 76.5% respectively. The FT-IR confirms that the components are physically mixed in NePCM composite, no chemical reaction appeared as no displacement of characteristic peaks or a new peaks appeared. TGA results showed the prepared nano-enhanced phase change material (NePCM) is stable. Thus, surface modification of MWCNT by using SDBS for PW can be the effective method to boost the overall performance of NePCM without losing its basic characteristics. Therefore, based on results, it can be concluded that the surface modified Paraffin/MWCNT NePCM is well suited for applications like energy storage, photovoltaic thermal system, and battery thermal management.